2011
DOI: 10.1002/eat.20896
|View full text |Cite
|
Sign up to set email alerts
|

The eating disorders examination in adolescent males with anorexia nervosa: How does it compare to adolescent females?

Abstract: Objective-The study aimed to explore the Eating Disorder Examination (EDE) for adolescent males with eating disorders (EDs) compared with adolescent females with EDs.Method-Data were collected from 48 males and matched on percent median body weight (MBW) and age to 48 females at two sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
86
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 43 publications
14
86
0
2
Order By: Relevance
“…Prior research has reported that eating-related scales such as the Eating Disorder Inventory and Eating Disorder Examination tend to have lower internal consistency reliability in males than in females [35,36]. Our study replicates this finding in the SCOFF.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Prior research has reported that eating-related scales such as the Eating Disorder Inventory and Eating Disorder Examination tend to have lower internal consistency reliability in males than in females [35,36]. Our study replicates this finding in the SCOFF.…”
Section: Discussionsupporting
confidence: 86%
“…As in other comparative studies, the scores for most items are consistently lower in men than in women [35,36]. The strong positive correlation between SCOFF score and body image concern supports that body dissatisfaction is a core symptom of ED in both genders, despite their different constructs of body dissatisfaction [35]. However, the SCOFF showed no correlations with anxiety and depression, which is evidence of discriminant validity.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In the Eating Disorders Examination (EDE-12), the global, shape, and weight concern scores in adolescent male patients were significantly lower compared to female patients, with effect sizes in the low-to-moderate range [35]. The authors concluded that the use of Eating Disorders Examination is acceptable in adolescent males, but certain questions may reflect symptoms that are atypical for males; current scoring ranges derived from female samples bore little resemblance to those of males with similar clinical presentations.…”
Section: Key Pointsmentioning
confidence: 99%
“…Therefore, studies of males with an ED may inform models of risk and resilience. Studies have shown that there are similarities in the clinical presentation of males and females with an ED (e.g., Carlat et al 1997;Bramon-Bosch et al 2000;Crisp 2006;Strober et al 2006;Button et al 2008) but some differences have been reported, such as a focus on muscle building rather than thinness (Fern á ndez- Aranda et al 2004;Woodside et al 2004;Darcy et al 2011), higher rates of exercise (Anderson and Bulik 2004), less weight concerns (Fern á ndez- Aranda et al 2004;Halmi et al 2005;Strober et al 2006) and higher rates of homosexuality (Carlat et al 1997). Men with EDs are reported to share elevated perfectionism and persistence with their female counterparts but show less harm avoidance and cooperativeness (Fassino et al 2001;Strober et al 2006;N ú ñ ez-Navarro et al 2011).…”
Section: Introductionmentioning
confidence: 99%